Farmers adaptation strategies to the effect of climate variation on yam production: a case study in Ekiti State, Nigeria (2013)
The study investigated farmers adaptation strategies to the effect of climate variation on yam production in Ekiti State with the specific objectives of assessing the socio-economic characteristics of farmers, farmers' climate related constraints, the adaptation strategies employed by farmers, and yam farmers' level of production across the years 2008, 2009 and 2010. A three - stage multistage sampling technique was used to select one hundred and fifty-one respondents from the list of contact farmers obtained from the state Agricultural Development Programme (ADP). Data collected through questionnaire were analysed using frequency counts, percentages, Chi-square, Pearson Product Moment Correlation and ANOVA. Results obtained showed that farmers in the study area were mostly males with a mean age of 53.9 years. Chi- square analysis revealed that there was a significant relationship between secondary occupation (X2= 14.068), farm size (x2= 99.597) and the level of production of yam farmers. Pearson product moment correlation indicated that there were significant and positive relationships between age (r = 0.160), adaptation strategies (r- 0.158) and level of production, while negative relationship was found between constraints (r = -0.173) and the level of yam production. ANOVA showed a significant difference in the level of production of farmers across the years; 2008, 2009 and 2010 (F- 212.7). Therefore, efforts should be geared towards developing and making available, yam setts that are tolerant to change in climate elements and weather extremes like flood and drought. This study also suggests the need for prompt weather information, increased research and development of innovation for sustainable yam cropping in the face of climate variation.